KONTRIBUSI KETERAMPILAN MENYIMAK BERITA TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VIII SMP PEMBANGUNAN LABORATORIUM UNP - Oktaviani, Monica; Rasyid, Yulianti (Universitas Negeri Padang, 2019)
ABSTRACTThere are three aims of this study. First, describe the skills of listening to the news of VIII grade students of the Middle School Development at the UNP Laboratory Development. Second, describe the writing text skills of VIII grade students of the Middle School Development in the Construction of the UNP Laboratory. Third, describe the contribution of listening to the news with the writing text skills of VIII grade students at the UNP Laboratory Development.The type of this research is quantitative in terms of descriptive methods. The design used in this study is correlational design. The population of this study was the eighth grade students of the Middle School Development of the UNP Laboratory which was registered in the 2017/2018 school year, it was 168 students.The sample in this study was determined by proportional random sampling of 25% of the population, namely 42 students. The research data is in the form of scores on the skills test results of listening to the news and scores on the results of the test writing news text skills. The instrument of this study is an objective test to measure news listening skills and performance tests to measure news text writing skills.The results of this study are three. First, the skills to write news texts of VIII grade students of the Middle School Development.The development of the UNP Laboratory is in accordance with the Good qualifications (B). Second, the skill of listening to the news text of VIII grade students of the Middle School Development of the UNP Laboratory Development in accordance with Good qualifications (B). Third, listening to news text skills contributed 32.72% to the news text writing skills of VIII grade students of the Middle School Development at the Construction of the UNP Laboratory. Kata Kunci: Kontribusi, Keterampilan Menyimak Berita, Keterampilan Menulis Teks Berita